The effectiveness of ultrasonography and ultrasonographic elastography in the diagnosis of carpal tunnel syndrome and evaluation of treatment response after steroid injection - EKİNCİ, GAZANFER; BUĞDAYCI, ONUR; GÜNDÜZ, OSMAN HAKAN (ELSEVIER IRELAND LTD, 2018)
Purpose: To evaluate if there is a place for ultrasonography (US) and ultrasonographic elastography (UE) in the diagnosis and follow up of carpal tunnel syndrome treatment. Materials and methods: The study was performed on 25 patients (study group) and 17 healthy volunteers (control group). Measured US and UE criteria were median nerve area (MNA), proximal median nerve area (pMNA), difference between MNA and pMNA (dMNA) and strain values of carpal tunnel content (CTC) and median nerve (MN). Patients in the study group were also evaluated using the Boston questionnaire, Visual Analogue Scale (VAS) and nerve conduction studies. Thirty-three wrists in 23 patients received steroid injections on the same day. Patients were re-evaluated 6 weeks after steroid injection. To establish a cut off value for MNA, ROC Curve analysis was used. Results: Mean MNA and dMNA values in the control group were significantly lower than in the study group (7.33 +/- 1.31 vs. 15.44 +/- 5.10; p = < 0.05 and 1.58 +/- 0.75 vs. 8.91 +/- 4.93; p = 0.00 respectively). Median nerve and CTC strain indices were significantly higher in the control group (p = 0.00 and p = 0.036). Decrease in MNA and dMNA values after treatment was meaningful (p = 0.00). While there was no significant change in MN elasticity, mean CTC strain index of the study group (4.680 +/- 1.664) decreased significantly after treatment (3.621 +/- 1.054 p = 0.002). This decrease in the CTC index was more pronounced in patients who benefited from treatment (p = 0.001). Conclusion: US and UE can be useful in the diagnosis of CTS and its response to treatment, if used together with clinical and electroneurophysiological tests.
Keywords: Carpal tunnel syndrome; Ultrasound; Ultrasound elastography; SUBSYNOVIAL CONNECTIVE-TISSUE; NERVE COMPRESSION; MEDIAN NERVE; SONOGRAPHY; ULTRASOUND; US; PATHOPHYSIOLOGY; CONDUCTION; COLLAGEN